Effects of metal contamination on the gene expression profile of two benthic species: Cerastoderma edule and Ruditapes philippinarum. Issue 1 (15th December 2017) - Rodrigues, Raquel; Lourenço, Joana; Pereira, Patrícia; Carvalho, Susana; Mendo, Sonia
Abstract: This study aimed to identify new biomarkers for metal exposure in two bivalve species. Suppressive Subtractive Hybridization (SSH) was employed to evaluate the transcriptomic response of Cerastoderma edule and Ruditapes philippinarum to metal pollution. Protein synthesis and catalytic activity were the most affected metabolic processes in C. edule and R. philippinarum, respectively. Also, different genes responded to the effect of contamination in each species. The different response observed in both species reinforces the importance of including more than one bioindicator species in risk assessment studies. These results provide the basis for new studies, which are necessary for further validation of the use of the identified genes as molecular biomarkers for metal exposure. Highlights: New biomarkers for metal exposure were investigated in two bivalve species. Suppressive Subtractive Hybridization technique was applied. The two species showed a differential response to metal contamination. Protein synthesis and catalytic activity were the most affected functions. Identified biomarkers require validation to serve as basis for further studies.